(untitled) (Emerging Indexing of Global Multidisciplinary Journal, 2025)
The Internet of Things has emerged as a dominant technological paradigm, enabling pervasive interconnection among heterogeneous devices across consumer, industrial, and critical infrastructure domains. The rapid growth in IoT deployments has intensified challenges related to communication efficiency, protocol interoperability, security resilience, and long-term energy sustainability. These challenges are exacerbated by the constrained nature of IoT devices, which operate under strict limitations in power, processing capability, and memory while remaining continuously exposed to dynamic and often hostile network environments. This article presents a comprehensive and integrative analysis of IoT ecosystems, focusing on communication protocol architectures, documented security vulnerabilities, and energy-aware operational strategies. Drawing strictly from the provided references, the study synthesizes industry reports, academic surveys, and protocol-level analyses to examine how protocol choices influence attack surfaces, system reliability, and energy consumption patterns. Particular attention is given to constrained protocol stacks, machine-to-machine communication models, routing and aggregation mechanisms, and embedded communication reliability in distributed energy systems. A descriptive and theory-driven methodology is employed to analyze interactions across system layers without reliance on mathematical modeling or visual artifacts. The findings reveal persistent trade-offs between scalability and security, as well as between energy efficiency and communication robustness. The discussion highlights structural limitations in current IoT designs and argues for vertically integrated, cross-layer approaches that align embedded communication reliability, network-level efficiency, and security enforcement. The article concludes by outlining future research directions aimed at developing resilient, secure, and energy-balanced IoT architectures capable of sustaining large-scale deployment.